Antimycobacterial and immunomodulatory activities of sorafenib in a preclinical mouse model of TB infection through CD4+CD25low and CD8+CD25low effector T cells - Rajmani, Raju S.; Surolia, Avadhesha (Frontiers in Immunology, 2025)
Tuberculosis is a communicable disease caused by Mycobacterium tuberculosis (Mtb). It is one of the major global public health problems that leads to a high morbidity and mortality rate. Drug resistance in Mycobacterium tuberculosis (Mtb) is another significant and persistent public health concern. The development of effective TB vaccines and treatments requires a better understanding of the intricate interactions between M. tuberculosis and host immunity. We previously reported that sorafenib (SRB) reduces bacterial growth by allosterically inhibiting ornithine acetyltransferase (MtArgJ), an essential enzyme in the arginine biosynthesis pathway of Mtb. Here, we report on the antimicrobial activity of sorafenib in preclinical mouse models of tuberculosis. Sorafenib is a potent drug approved by the Food and Drug Administration (FDA) for treating several types of cancer. The current study is focused on the immunomodulation that SRB induces in the host, specifically the immunological response that is triggered to combat the pathogenicity and survival of the bacteria.Here, we show that SRB significantly sterilizes the bacterial burden in chronic infection animal models of tuberculosis by reducing the number of Mtb-susceptible alveolar macrophages (AMs), and that SRB is more effective when combined with rifampicin (RIF). In the current study, we documented a new immune modulatory characteristic of sorafenib that, upon SRB treatment, markedly increased effector T cells (Teff - CD4+CD25low and CD8+CD25low) activity and decreased regulatory T cells, the immunosuppressive T cells (Treg- CD4+CD25high and CD8+CD25high) function. In conclusion, our studies revealed that SRB is beneficial for both boosting an efficient T cell response and lowering the tubercular load.